Social theory and current affairs: a framework for intellectual engagement1. (27th April 2014) - Stones, Rob
Abstract The paper aims to facilitate more adequate critical engagement with current affairs events by journalists, and with current affairs texts by audiences. It draws on social theory to provide the intellectual resources to enable this. The academic ambition is for the framework to be adopted and developed by social thinkers in producing exemplary critical readings of news and current affairs texts. To this end it is offered as a research paradigm. The paper situates its argument in relation to the wider literature in media and cultural studies, acknowledging the subtle skills required to appreciate the relative autonomy of texts. However, it draws attention to the lack of an adequate perspective with which to assess the frames, representations, and judgments within news and current affairs texts. To address this lacuna it proposes the conception of a social‐theoretical frame, based on a number of meta‐theoretical approaches, designed to provide audiences with a systematic means of addressing the status and adequacy of individual texts. Social theoretical frames can reveal the shortcomings of media framing of the contextual fields within which news and current affairs events take place. Two illustrative case studies are used to indicate the value and potential of the approach: the analysis of a short newspaper report of the return of protesters to Cairo's Tahrir Square in 2011, and a critique of four current affairs reports from various genres on the political turmoil in Thailand leading up to the clashes of May 2010.